Urological and Gynaecological Chronic Pelvic Pain : Current Therapies - Moldwin, Robert M. (Springer International Publishing : Imprint: Springer, 2017)
This text is designed for those clinicians who feel comfortable diagnosing these illnesses and wish to enhance their knowledge base and skill set regarding treatment options. Referrals for pelvic pain are common in urological and gynaecological practice; and may lead to varied diagnoses such as interstitial cystitis/bladder pain syndrome, chronic prostatitis/chronic pelvic pain syndrome, pelvic floor dysfunction, chronic orchialgia, and vulvodynia. To make matters more complex, each of these conditions is frequently associated by co-morbidities. The text is unique in being organized by the multiple and multifaceted therapies that are available, rather than by specific disorders. The text is richly illustrated with multiple diagrams, figures, and tables, making it the "go to" and "how to" reference for patient treatment.
Keywords: Medicine.; Urology.; elektronické knihy; electronic books